(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2025)
A critical feature of our interconnected world seems particularly relevant nowadays: the inherent tension between glocal reality and a rigid geopolitical order. In a world that appears increasingly closed within national or regional borders, we are faced with a transformation of the relationship between global and local and the intellectual, cultural, and political challenges that such a transformation brings. The perpetual endeavour to traverse the chasm between glocal tensions and the concrete realities of heterogeneous societies, cultures, and political terrains is of paramount importance.